Rainfall Characteristic on the Slopes of Mount Merapi Region (Empirical Formula, Duration, Distribution, And Critical Line Woro River) - Pudak Juni Laksana (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Debris flow on the slopes of Mount Merapi area became a serious natural disasters because it has great destructive force and velocity. Rainfall with a certain intensity and duration is one component triggering debris flow. Rainfall has variability of the temporal and spatial characteristics influenced by various factors, such as topography and climate. Dharma (2012) suggested to define the characteristics of the intensity of rainfall using rainfall data with a shorter duration with statistical tests to establish the best empirical IDF formula. This research was using of 30 minutes rainfall data for short duration (<3 hours) and a spreadsheet software representing duration and distribution of the rainfall. The most appropriate rainfall intensity formula was done by the empirical IDF formula, i.e. Sherman, Kimijima, Hasper and Mononobe. Rainfall intensity analysis applied Frequency Analysis Software (based on Microsoft Excel). Debris flow occurrence was analyzed using MLIT for method A to establish standard rainfall index. Sherman formula performed the best fit to the IDF characteristics of rainfall in the region of the slopes of Mount Merapi. Rainfall distribution pattern showed high intensity rainfall in the first hour and then decreased in the next hour which means distribution for the duration of 3 hours, 12%, 28%, 25%, 16%, 12%, and 7%, respectively with an interval of 30 minutes. Based on critical line, 5 mm of standard rainfall index was gained in the case of warning (R1) and 28 mm in the case of evacuation (R2).